Analysis of occlusal and articulating ratios of jaws in patients after prosthetics with various types of fixed structures - N. Proshchenko (Kazimierz Wielki University, 2024)
A new trend in medicine is the introduction of digital technologies in dentistry, with the help of which patients with partial loss of teeth achieve the necessary occlusal ratios of the jaws and aesthetic results. Modern processes for manufacturing fixed dental prostheses shorten the treatment period and accelerate the adaptation process, and the introduction of digital processes at the stage of planning and manufacturing of fixed structures makes it possible to increase the productivity of dentists-orthopedics. Aim: to study the peculiarities of the distribution and magnitude of the contact pressure that occur on the surface of the teeth in patients with different types of occlusion. Materials and methods. In order to solve the set goal, we performed clinical and laboratory examination of patients with defects of the crown part of the tooth before prosthetics and 6 months after prosthetics. Of these: 80 (48.5%) patients were prosthetically implanted with fixed structures manufactured in the laboratory, and 85 (51.5%) were digitally implanted. The total number of patients with crown defects on the upper jaw was 84 (50.9%) and 81 (49.1%) on the lower jaw. Of them, 85 (48.5%) were women and 80 (51.5%) were men. To study the peculiarities of the distribution and magnitude of the contact pressure that occur on the surface of the teeth in the studied patients with different occlusion variants, we used the T-Scan computer analysis system of occlusion. Research results. Bridge-like prostheses made by the analog method have certain disadvantages that persist throughout the registration period. The occlusal pattern of load on certain groups of teeth worsens. These are excessive overloads of the lateral group of teeth in each adaptation period of registration. Weakened or even absent occlusal contacts of the front group of teeth. After selective grinding of the teeth, the situation does not change significantly. At each of the stages, the fissure-tuberous contacts are corrected, which improves the occlusal balance, but turns point contacts into flat ones. This in turn leads to possible prolonged chewing time and myofascial imbalance. as well as overloading of the temporomandibular joint. At the same time, it should be noted that the time of closing and opening of tooth rows remains within the physiological norm. Conclusions. It was established that patients who had temporary bridge-like fixed structures manufactured by the analog method had an underestimation of the interalveolar height, which resulted in premature contact of the teeth with their subsequent overload. Preservation during the entire period of registration of supracontacts indicates a lack of adaptation to them and an increase in the time of the dentist-orthopedic doctor for selective grinding and interference with the physical properties of fixed structures.